PENGARUH PERPUTARAN KAS, PERPUTARAN PIUTANG DAN PERPUTARAN PERSEDIAAN TERHADAP RENTABILITAS EKONOMI PADA PT KIMIA FARMA - Aliffia Aliffia; Nani Mulyani (LPPM Universitas Bina Bangsa, 2023)
This study aims to determine the effect of Cash Turnover, Accounts Receivable Turnover and Inventory Turnover on Economic Profitability. This study used samples from the Quarterly Financial Statements of PT Kimia Farma, Tbk for the period 2010 to 2021. There were 48 samples used in this study using a non probability sampling method. The data used in this research is secondary data. Research data were obtained from the website www.kimiafarma.co.id and idx.co.id data. The data obtained and collected were then processed using the SPSS version 26 application. The results of the F test showed that Cash Turnover, Accounts Receivable Turnover and Inventory Turnover simultaneously had a significant effect on Economic Profitability. Meanwhile, in the partial test of Cash Turnover and Accounts Receivable Turnover, it has no effect on Economic Profitability and Inventory Turnover has a positive effect on Economic Profitability. Based on the determination coefficient test (R2) it shows that the Adjusted R Square value is 0.799 meaning that Cash Turnover, Accounts Receivable Turnover and Inventory Turnover can be a benchmark for companies in obtaining good economic profitability of 79% and the rest can be explained by other factors that are not known in this study